The Mapping of Meaning Components of Phrases about Plants in Indonesian and English Translation - I Gede krisna Wedhana C; I Made Rajeg; I Nengah Sudipa (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2021)
This research aims at finding the types of procedures applied in translating Indonesian plant phrases into English, as well as analyzing the mapping of meaning components of the phrases from the source language to the target language. The data source is a bilingual biology textbook for senior high school students. The data in this study are in the form of two-word noun phrases about plants. Data were collected using observation method, random sampling method, and note-taking technique. The data were analyzed by using theories of translation procedures proposed by Vinay and Darbelnet and Natural Semantic Metalanguage. The result showed that the types of translation procedures applied are transposition and literal translation. The meaning components of the phrases of the source language are mostly transferred to the target language.